100 ideas for teaching citizenship - Davies, Ivan. (London : Continuum, 2007)
The Continuum One Hundreds series gives 100 invaluable and practical ideas for teachers of all levels. Citizenship has recently become a compulsory subject within secondary education. Ian Davies provides teachers with 100 practical ideas on how to incorporate citizenship education into all aspects of teaching. With ideas ranging from where to find the best resources to ideas for fun classroom activities.
Keywords: Citizenship -- Study and teaching